Psychomotor hyperactivity in children - Budziejko, Blanka; Białkowska, Aleksandra; Cywińska, Oliwia; Kurtyka, Daria; Dziarkowski, Dariusz; Gawrych, Szymon; Różański, Gracjan; Dobosiewicz, Anna Maria; Badiuk, Nataliia (Journal of Education, Health and Sport, 2018)
Psychomotor hyperactivity syndrome with attention deficit disorders is a neurodevelopmental disorder, which is manifested by excessive mobility and impulsivity preventing normal functioning in society. This leads to deconcentration during the basic activities of everyday life. The first symptoms of the disease may appear in the early pre-school period of childhood, but they may not be sufficiently noticeable yet. The severity of symptoms may depend on the situation and may evolve with the age of the child. The etiology of the disease is not clear, which makes it elusive to identify the cause. However, we know that ADHD affects three times more boys than girls. There is a concept that statistics on increased male morbidity may be due to inheritance, as the female sex is the carrier of the gene responsible for the occurrence of hyperactivity. The aim of this paper is to describe the characteristics of hyperkinetic disorder, including symptoms, etiology and some forms of treatment.